Feeling misidentified: Understanding migrant's readiness to engage in health care screening. (September 2019) - Hendy, Jane; Vandrevala, Tushna; Ahmed, Ayesha; Kelly, Claire; Gray, Lucy; Ala, Aftab
Highlights: Screening interventions primarily use socio-cognitive theories. We widen the theoretical lens to explain migrant's uptake of health screening. We explore community, support networks and issues of identity. Migrant screening uptake is related to feeling misidentified or misunderstood. The results can constructively re-shape future screening practices.